Bone and kidney toxicity induced by nucleotide analogues in patients affected by HBV-related chronic hepatitis: a longitudinal study. (18th December 2014) - Maggi, Paolo; Montinaro, Vincenzo; Leone, Armando; Fasano, Massimo; Volpe, Anna; Bellacosa, Chiara; Grattagliano, Vito; Coladonato, Laura; Lapadula, Giovanni; Santantonio, Teresa; Angarano, Gioacchino
Abstract: Objectives: Nucleotide analogues may promote renal and bone toxicity. The aim of the present study was to evaluate markers of osteorenal toxicity in patients affected by hepatitis B virus-related chronic hepatitis treated with lamivudine plus adefovir who were switched to tenofovir. Patients and methods: We evaluated 60 consecutive patients at the time of the switch of treatment and after 1, 3, 6, 9 and 12 months. The mean baseline estimated glomerular filtration rate (eGFR) was 89.3 ± 19.0 mL/min/1.73 m 2 . Results: During the study period we observed a reduction in mean eGFR up to 6 months after switching to tenofovir, and this remained stable for the last two timepoints. At the end of study, the mean eGFR was 82.6 ± 21.5 mL/min/1.73 m 2, a reduction of 7.5%. The mean baseline proteinuria was 202.6 ± 237.6 mg/24 h. Microhaematuria was observed in 22.6% of patients and hypophosphataemia in 18.6%. After 1 month of tenofovir, we observed a worsening of serum phosphate and parathyroid hormone levels, haemoglobinuria and 24 h proteinuria. After 3 and 12 months of tenofovir, these data tended to recover to baseline levels. A total of 92.6% of patients at baseline had hypovitaminosis D. After supplementation with cholecalciferol, this percentage decreased significantly. We observed a reduced bone mineral density (BMD) in 52.7% of patients at baseline; this increased to 77.8% after 6 months of tenofovir, but at the last timepoint the percentage of patients with a reduced BMD had fallen to a level above the baseline. Conclusions: In conclusion, patients exposed to lamivudine plus adefovir showed relevant osteorenal damage. The switch to tenofovir provoked a slight reduction in eGFR that stabilized after 6 months. The reduced BMD at baseline did not worsen under tenofovir treatment.